Loss sharing in central clearinghouses: Winners and losers - Christian Kubitza; Loriana Pelizzon; Mila Getmansky (European Central Bank (ECB), 2023)
Central clearing counterparties (CCPs) were established to mitigate default losses resulting from counterparty risk in derivatives markets. In a parsimonious model, we show that clearing benefits are distributed unevenly across market participants. Loss sharing rules determine who wins or loses from clearing. Current rules disproportionately benefit market participants with flat portfolios. Instead, those with directional portfolios are relatively worse off, consistent with their reluctance to voluntarily use central clearing. Alternative loss sharing rules can address cross-sectional disparities in clearing benefits. However, we show that CCPs may favor current rules to maximize fee income, with externalities on clearing participation.
Keywords: G18; G23; G28; G12; 330; Central Clearing; Counterparty Risk; Loss Sharing; OTC markets; Derivatives